ANALISIS PERILAKU HEDONISME MAHASISWA DALAM PEMBELIAN SKINCARE SECARA ONLINE SELAMA MASA PANDEMI - Beatrice Karmila Devi; Bunga Widiantoro Putri; Irene Iola Auxilia Benedecas; Chrismada Melvin Teodes Sitepu; Putri Nastiti (LPPM - STIE SAKTI ALAM KERINCI, 2022)
The current Covid-19 pandemic has an impact on various sectors of life, especially in the economic and shopping sectors. During the pandemic, many students stayed at home and conducted lectures online. The existence of e-commerce provides a sense of security in transactions, where students can buy various kinds of their needs. However, with the existence of e-commerce, students make purchases that are not controlled. Problems like this will change the behavior of students to live hedonism and behave consumptively. Supported by the widespread sense of wanting to beautify themselves among students which can lead to excessive online skincare purchases. Based on the above phenomenon, the researcher wants to analyze the consumptive behavior and hedonism of students. Therefore, this study aims to determine the factors that cause the tendency of hedonistic behavior among students to purchase skincare online. The method used is the Hedonic Motivation System Adoption Model (HMSAM) and Descriptive Analysis. The target of this research is 120 students from Atma Jaya University, Yogyakarta. The result of the study found that the e-commerce convenience (Perceived Ease of Use) was able to increase the shopping intensity of Atma Jaya University Yogyakarta students, resulting in hedonism and consumptive behavior.